GAMBARAN KEPRIBADIAN SISWA SEKOLAH DASAR DI DESA CIHERANG, KABUPATEN CIANJUR, JAWA BARAT - Zamralita , Zamralita; Basaria, Debora; Fahlevi, Reza; Margaretha, Jane; Widyastuti, Philomena Esti (Fakultas Psikologi Universitas Tarumanagara, 2025)
Personality development in elementary school-aged children serves as a crucial foundation for shaping character, thought patterns, and social behavior that will carry into adolescence and adulthood. Understanding the personality traits of elementary students is an important factor in predicting their academic achievement. The dynamics of personality development, particularly in rural areas, possess unique and complex characteristics. Factors such as close-knit social environments, strong local cultural values, and limited access to educational facilities play a significant role in shaping children's personalities in these regions. Ciherang Village, located in Cianjur Regency, West Java, is one such rural area with distinct social and educational characteristics. In the context of primary education, challenges such as limited infrastructure, restricted access to learning resources, and a shortage of qualified educators can influence both the learning process and the psychological development of students. Amid these conditions, understanding students' personality traits becomes increasingly vital. This study aims to provide an overview of the personality profiles of elementary school students in Ciherang Village using a descriptive quantitative approach. A total of 154 students from several elementary schools in the village participated in this research. The instrument used was a questionnaire consisting of 48 items assessing five personality dimensions: Openness, Conscientiousness, Extraversion, Agreeableness, and Neuroticism. The analysis revealed that most participants scored high in Agreeableness and low in Neuroticism. These findings suggest the need for implementing collaborative learning systems and relational approaches to support students' optimal personality development.